(untitled) (World Bulletin of Social Sciences, 2025)
The article examines the audience’s perception of the image of an anchor of an informational TV program as a significant communicative resource in today’s media reality. Theoretical foundations of the study are based on works of scholars who emphasize the key role of the TV presenter’s personality in the process of television communication. The anchor’s image is analyzed as a set of visual, speech, and behavioral characteristics influencing the perception of information and the level of audience trust. An empirical study conducted through an online survey among TV viewers in the Republic of Uzbekistan identified the most important qualities of an anchor from the audience’s perspective. Results show that the key factors in forming a positive image are charisma, speech manner, and the ability to deliver information clearly and convincingly. The collected data confirms the thesis about the importance of the personal characteristics of a TV anchor as a mediator between the audience and informational content.